Morphological Control of Mesoporous Silica Nanoparticles and Their Application for Foam Stability - Bon Yoon, Suk; Yoon, In-Ho; Kim, Chorong; Jung, Chong-Hun; Kim, Seonbyeong; Choi, Wang-Kyu; Moon, Jei-Kwon (Asian Journal of Chemistry, 2014)
Mesoporous silica nanoparticles with various sizes and shapes were synthesized by varying the amount of the ammonia solution as a basic catalyst and cetyltrimethylammonium bromide (CTABr) as a cationic surfactant. It was found that the particle size and shape were strongly dependent on the amount of the ammonia solution and cetyltrimethylammonium bromide. While the mesoporous silicas exhibited the small sizes and irregular shapes when using a low concentration of the ammonia solution, the rod-like shapes with well-ordered pore structures as a MCM-41 were synthesized under a strong basic condition. Resulting materials showed high specific surface areas (813-919 m2/g), large pore volumes (0.60-1.66 cm3/g) and uniform pore sizes (1.87-2.36 nm). The mesoporous silica nanoparticles with different sizes were used to investigate the effect of the nanoparticles on the foam stability. The results showed that both foam volume and liquid volume in the foam were enhanced when using a smaller size and lower density of the mesoporous silica nanopartcles.